Islam Moderat Dalam Dinamika Kehidupan Masyarakat Indonesia: Analisis Bibliometrik - Maulana, Andre; Baharudin, Baharudin; Bahri, Saiful; Octafiona, Era; Shabira, Qonita (Faculty of Islamic Sciences, Raden Rahmat Islamic University Malang, 2025)
This study aims to analyze the development of moderate Islam in Indonesian society through a bibliometric approach, focusing on scholarly literature published between 2019 and 2024. Moderate Islam has become a vital pillar in maintaining social harmony, promoting interfaith tolerance, and reducing the potential for radicalization, particularly among the younger generation. Based on the bibliometric analysis, there has been a notable increase in the number of publications related to moderate Islam, peaking in 2021, although a decline was observed in subsequent years. This study highlights the role of moderate Islam in shaping policies that emphasize interreligious dialogue and reinforce the values of inclusivity in social life. Furthermore, moderate Islam plays a significant role in promoting social balance, fostering a more just society, and encouraging the active participation of women in the public sphere of religion. Through bibliometric analysis, this research identifies trends and patterns in publications related to moderate Islam and illustrates its contribution to developing social and political stability in Indonesia. Overall, the findings of this study offer valuable insights for policymakers, academics, and the public in strengthening the values of moderation in religious life across Indonesia. Keywords: Moderate Islam, Bibliometric Analysis, Social Harmony in Indonesia